Systematic Literature Review: Kemampuan Berpikir Kreatif Matematis - Ramal Fitra Ramal; Meiliasari Meiliasari; Lukman EL Hakim (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This study discusses the meaning and indicators of mathematical creative thinking ability. The research method used is library research. Based on the results of the study it was found that the ability to think creatively mathematically is the ability to solve open-ended mathematical events by presenting various new ideas. The indicators for measuring the ability to think creatively mathematically are fluency, flexibility, originality, and elaboration.